ANALISIS PENGELOLAAN AKUNTANSI ASET PADA BADAN KESATUAN BANGSA DAN POLITIK PROVINSI SULAWESI UTARA - Tani, Lovenhia Claudya; Manossoh, Hendrik; Wokas, Heince Rudy Nicky (Universitas Sam Ratulangi, 2020)
Asset accounting is one of the most important components in order to achieve good governance. Asset accounting has a management that must comply with the applicable rules. The purpose of this research is to know how to manage the asset accounting at The National and Politics Board of North Sulawesi Province by implementing the accrual based government accounting standard, using the analysis method. Results of the study of The National and Politics Board of North Sulawesi Province demonstrate the implementation of the management process of asset goods accounting on The National and Politics Board of North Sulawesi Province on every sub system has not been effectively affected overall. Based on the results the authors give advice on the unity of the nation and politics to continue to maintain or improve the performance in carrying out the mandate of law.